Original elements and typification of the names included in the Ononis tridentata complex (Fabaceae) - Ferrer-Gallego, P. Pablo (Phytotaxa, 2023)
A nomenclatual revision of the Ononis tridentata L. complex in the Iberian Peninsula is presented and the typification of several names, viz. O. barrelieri Dufour, O. crassifolia Dufour ex Boissier, O. crassifolia var. intricata Willkomm, O. tridentata var. angustifolia Lange, O. tridentata var. canescens Lamarck ex Candolle, O. tridentata var. dentata Willkomm, O. tridentata var. edentula Willkomm, O. tridentata var. integrata Amo, O. tridentata f. intermedia Lange, O. tridentata var. intermedia f. erecta Willkomm, and O. tridentata var. latifolia Lange, is discussed. The names are lectotypified using specimen preserved at BORD, COI, G, and P herbaria. A “second-step” epitypification is proposed for the name O. tridentata according to Art. 9.17 of the ICN. The lectotype of O. crassifolia is designated from a specimen at P. The names O. barrelieri, O. crassifolia var. intricata, O. tridentata var. canescens, and O. tridentata f. intermedia, and O. tridentata var. intermedia f. erecta should be treated as synonyms of O. tridentata subsp. arbuscula, comb. & stat nov. due to the epitype designated by Förther in 1997 for O. tridentata, and not as synonyms of O. tridentata Linnaeus s.str. as they have traditionally been considered.